The Fan Lifestyle on the Example of Soccer Fans - Tomasz Brzana; Leonard Nowak; Maria Alicja Nowak (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
The aim of this study was to investigate chosen aspects of the lifestyle of soccer fans. Methods. The study was conducted among 200 fans. In the study a diagnostic survey was employed, with the use of the techniques of questionnaire, interview, document analysis and participant observation. In order to draw statistical conclusions, the trait frequency, the independence χ2 test and multiple correspondence analysis were used. Results. The community of active fans is characterized by various kinds of behavior. Fans aged 15–19, for whom important motives for cheering were the opportunity to be with a group and a sense of connectedness, as well as a sense of strength and power, declared consumption of alcoholic beverages before matches. For fans aged 20–24, who more often practiced combat sports and exercised in the gym, an important motive for cheering was the opportunity to meet their friends and let off steam during the match. They regarded devastation of sports facilities and burning scarves as acts of hooliganism. Fans aged 25–29, and 30 or above admitted that they sometimes consumed alcoholic beverages before the game. Conclusions. There is a necessity to educate children and youth in sports cheering.